2016
DOI: 10.1002/jrs.4997
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of archaeometallurgical artefacts by means of portable Raman systems: corrosion mechanisms influenced by marine aerosol

Abstract: This work focuses on the analytical study of eight medieval metallic artefacts discovered during the archaeological excavations of the Ereñozar necropolis (13th century, Basque Country, Spain). As the conservation state of archaeological objects is closely related to the characteristics of the burial environment, chromatographic analysis was performed with the aim of quantifying the soluble salt content of the burial ground. Moreover, portable systems were used for the elemental and molecular characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
(69 reference statements)
1
10
0
Order By: Relevance
“…Akaganeite is an oxy‐hydroxide that is formed when the artifacts are in contact with chloride‐rich environments; the Raman spectrum of akageneite shown in Figure is almost identical to one reported by Neff et al It is known that chlorides are the most harmful stressor for archaeological irons and must be removed as soon as the pieces are extracted from the burial …”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Akaganeite is an oxy‐hydroxide that is formed when the artifacts are in contact with chloride‐rich environments; the Raman spectrum of akageneite shown in Figure is almost identical to one reported by Neff et al It is known that chlorides are the most harmful stressor for archaeological irons and must be removed as soon as the pieces are extracted from the burial …”
Section: Resultssupporting
confidence: 72%
“…This could mean that the treatment has not reacted properly with the material of the archaeological piece or the loss of the applied protector layers, probably due to the incompatibility between materials and the aggressive environment of the building, set in front of the sea and affected by the continuous marine aerosols. Anyway, it is demonstrated that the best treatment for an iron buried tool exposed to the atmosphere is that which accelerates the transformation of lepidocrocite/akaganeite into goethite …”
Section: Resultsmentioning
confidence: 99%
“…The indispensable condition to ensure proper conservation of ancient iron artefacts is to reach a state of chemical and physical balance with the environment in which they are preserved [1].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the sensitivity of each system for the characterization of Fe‐based and Cu‐based corrosion phases was compared. In addition, the information obtained from both chromatographic and spectroscopic techniques allows the modeling of the chemical reactions that led to the formation of the identified degradation products . Wang et al presented a Raman study of Yuan Qinghua porcelain that highlighted dendritic CoFe 2 O 4 crystals in blue decorations.…”
Section: Art and Archaeologymentioning
confidence: 96%
“…In addition, the information obtained from both chromatographic and spectroscopic techniques allows the modeling of the chemical reactions that led to the formation of the identified degradation products. [122] Wang et al presented a Raman study of Yuan Qinghua porcelain that highlighted dendritic CoFe 2 O 4 crystals in blue decorations. This marks the first time that spinel crystals, with a composition close to cobalt ferrite were observed as the main constituent of the dark spots in blue decors of Qinghua porcelains.…”
Section: Other Coherent Nonlinear Techniquesmentioning
confidence: 99%